Online Piracy and Copyright Protection Through Internet (A Critical Review For The Intellectual Rights and Obligations Balance - Makarim, Edmon (Indonesian Journal of International Law, 2012)
Internet as a new communication medium, is the result the information and communication technology convergence, which came in the form of an electronic system. In the intellectual property rights perspective especially in copyright context, an intellectual creation is protected as one’s property (a bundle of rights) that includes moral rights and economic rights. IPR protection paradigm actually dominated by private communication paradigm, so any communication of the intellectual work is the author's rights. Meanwhile, paradigm in the Internet is a mass communication, so the delivery and retrieval of any information communicated on the Internet is considered as the rights of every human being. These differences seemed lead to the ineffectiveness of any attempt to restrict copying or access to the use of a digital work.